Baju Kurung or Baju Kebaya? Framing the History of the Brunei Women’s Fashion (Paramita: Historical Studies Journal, 2022)
This article investigates the relationship between women’s fashion in Brunei Darussalam and the historical factors that influenced the evolution of the former in the 1960s, the 1970s, and the 1980s. By employing a qualitative visual analysis method, this study analyzed photographs of Brunei women published in the national newspaper Pelita Brunei from the 1960s to the 1980s. Document review and thematic coding analysis were employed to frame and examine the historical context within which Brunei women’s fashion experienced a significant spectrum of trends. The findings of this study indicate that the evolution of women’s fashion in the 1960s and 1970s was primarily due to a combination of domestic and external influences such as the growth of popular entertainment, education, government’s role, and, to a considerable extent, the societal expectation towards women and the Islamic resurgence in the Southeast Asian region. In comparison, in the 1980s, Brunei women’s fashion was characterized strongly by Islamic ideals due to the declaration of Melayu Islam Beraja (MIB) as the State Philosophy, concomitant to Brunei’s independence in 1984. Based on these findings, this article proposes some potential research directions that can be pursued by future research. Artikel ini menyelidiki hubungan antara busana wanita di Brunei Darussalam dan faktor-faktor sejarah yang memengaruhi evolusi gaya busana wanita di tahun 1960-an, 1970-an, dan 1980-an. Dengan menggunakan metode analisis visual kualitatif, penelitian ini menganalisis foto-foto perempuan Brunei yang dimuat di surat kabar nasional Pelita Brunei dari tahun 1960-an hingga 1980-an. Tinjauan dokumen dan analisis pengkodean tematik digunakan untuk membingkai dan memeriksa konteks historis di mana mode wanita Brunei mengalami spektrum tren yang signifikan. Temuan penelitian ini menunjukkan bahwa evolusi mode wanita pada tahun 1960-an dan 1970-an terutama disebabkan oleh kombinasi pengaruh domestik dan eksternal seperti pertumbuhan hiburan populer, pendidikan, peran pemerintah, dan, sampai batas tertentu, masyarakat. harapan terhadap perempuan dan kebangkitan Islam di kawasan Asia Tenggara. Sebagai perbandingan, pada tahun 1980-an, busana wanita Brunei sangat dicirikan oleh cita-cita Islam karena deklarasi Melayu Islam Beraja (MIB) sebagai Filosofi Negara, bersamaan dengan kemerdekaan Brunei pada tahun 1984. Berdasarkan temuan ini, artikel ini mengusulkan beberapa penelitian potensial. arah yang dapat ditempuh oleh penelitian masa depan. Cite this article: Kamaluddin, K., Kumpoh, A. (2022). Baju Kurung or Baju Kebaya? Framing the History of the Brunei Women’s Fashion Paramita: Historical Studies Journal, 32(2), 180-190. http://dx.doi.org/10.15294/paramita.v32i2.34526